2012
DOI: 10.1667/rr2681.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spontaneous DNA Damage in Lymphocytes of Healthy Adult Individuals from High-Level Natural Radiation Areas of Kerala in India

Abstract: Inhabitants of the high-level natural radiation areas (>1 mSv year(-1)) of Kerala in southwest India were evaluated for basal damage (spontaneous DNA strand breaks and alkali-labile sites) by the alkaline comet assay and oxidative DNA damage (ENDO III- and hOGG1-sensitive sites) by the enzyme-modified comet assay. Of the 67 adult male subjects studied, 45 were from high-level natural radiation areas and 22 subjects were from a nearby normal-level natural radiation area (≤1 mSv year(-1)). Basal damage due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Our data showed an over-expression of ten FA pathway proteins (ATR, BLM, BRCA2, DPOLN, FANCA, FANCI, FANCM, MLH1, RMI2, and XPF) in HLNRA individuals. Constitutive activation of several canonical and non-canonical FA proteins seen in the present work may thus, provide a rationale for lower incidence of basal level DNA damage in lymphocytes of HLNRA individuals from Kerala as seen with earlier studies 46,47 . On the other hand, three primary pro-survival signaling pathways identified by KEGG namely, PI3K-Akt signaling pathway, HIF-1 signaling pathway and Rap1 signaling pathway showed a radiation dose-specific enrichment (P ≤ 0.05, Fisher's exact test) (Fig.…”
Section: Pathway Enrichment Of Differentially Regulated Proteinssupporting
confidence: 73%
“…Our data showed an over-expression of ten FA pathway proteins (ATR, BLM, BRCA2, DPOLN, FANCA, FANCI, FANCM, MLH1, RMI2, and XPF) in HLNRA individuals. Constitutive activation of several canonical and non-canonical FA proteins seen in the present work may thus, provide a rationale for lower incidence of basal level DNA damage in lymphocytes of HLNRA individuals from Kerala as seen with earlier studies 46,47 . On the other hand, three primary pro-survival signaling pathways identified by KEGG namely, PI3K-Akt signaling pathway, HIF-1 signaling pathway and Rap1 signaling pathway showed a radiation dose-specific enrichment (P ≤ 0.05, Fisher's exact test) (Fig.…”
Section: Pathway Enrichment Of Differentially Regulated Proteinssupporting
confidence: 73%
“…Most importantly, the unique feature of HLNRA of Kerala coast is the non-uniform distribution of monazite in the beach sand which leads to varying level of background radiation (<1.0 to 45mGy/year) along the 55 km long stretch allowing us to investigate in-vivo dose response, if any at various biological end points. Several epidemiological (congenital malformation, cancer incidence etc) and biological studies carried out in this population have not revealed any significant difference between NLNRA and HLNRA population [ 9 , 11 , 16 , 17 , 18 , 20 , 22 ]. However, recent studies have shown a lower induction and efficient repair of DNA damage in HLNRA individuals [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 79%
“…So far, no significant changes are observed at phenotype level. This population has also been investigated for several biological end points such as chromosome aberrations, micronuclei, telomere length measurement and quantitation of DNA damage [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].None of the above DNA damage end points have shown significant difference between the population from HLNRA and the adjacent normal level natural radiation areas (NLNRA). The spontaneous level of DNA double strand breaks (DSBs) has not shown any increase in DSBs, rather showed marginal reduction in HLNRA individuals belonging to background dose group >5mGy/year [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…If humans adapted better to higher than lower levels of chronic irradiation, then without going into details of such mechanisms, one would have to accept that at least the higher level of radiation, as in Ramsar, is relatively well tolerated. In another HNBR study in Kerala, India, the incidence of DNA damage per person decreased with age, whereas in the control population, the incidence of DNA damage increased with age, as predicted (Kumar et al 2012). Moreover, a recent study (Fliedner et al 2012) reviewed the data on dogs that were kept during their entire life in an artificial high background of g-radiation (Co-60).…”
Section: Natural Background Radiation In Selected Studies In Humansmentioning
confidence: 94%